Elektronsko učno orodje v osnovni šoli - Bele Tominc, Lada (Uporabna informatika (Ljubljana), 2000)
The main purpose of the paper is informative. The basic characteristics of theeducation in the primary school, which influence the design of the electronic learning tools, are presented in the first part of the paper. The model of the electronic learning tool, dealing with the subject of geography in the fifth class of the primary school, is presented in the second part of the paper. The tool could be very useful in the process of distance learning, as well as an addition to the classical teaching and learning and as a source of higher motivation for the children.
Keywords: elektronsko učno orodje; model elektronskega učnega orodja; osnovna šola; spoznavanje družbe